Symbolic communication as speech in United States Supreme Court jurisprudence - Machaj, Łukasz (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The First Amendment to the United States Constitution forbids government to pass any law which abridges freedom of speech. Notwithstanding the absolute tenor of the clause, this guarantee is clearly not limitless; its boundaries are established mainly in the course of Constitutional adjudication. The United States Supreme Court has extended free speech guarantees to so-called symbolic speech, i.e. to nonverbal expression of ideas, views or emotions. The article analyzes basic criteria and limits of First Amendment protection with respect to such instances of (alleged) symbolic communication as flying a red flag, refusing to salute the U.S. flag, wearing a black armband, silently protesting segregation rules, burning a crucifix, burning a draft card, sleeping in a park and nude dancing. In some cases the level of protection given to symbolic speech is deemed analogous to that accorded to written or oral expression; in other cases the Supreme Court applies the so-called O’Brien standard, which is an instrument designed specifically for judging laws relevant to this mode of communication.
Keywords: wolność słowa; Stany Zjednoczone Ameryki Północnej; Pierwsza Poprawka do Konstytucji USA; komunikacja symboliczna